Associations between education and dementia in the Caribbean and the United States: An international comparison. Issue 1 (5th September 2021) - Li, Jing; Llibre‐Guerra, Jorge J.; Harrati, Amal; Weiss, Jordan; Jiménez‐Velázquez, Ivonne Z.; Acosta, Daisy; Llibre‐Rodriguez, Juan de Jesús; Liu, Mao‐Mei; Dow, William H.
Abstract: Introduction: Despite high dementia prevalence in Hispanic populations globally, especially Caribbean Hispanics, no study has comparatively examined the association between education and dementia among Hispanics living in the Caribbean Islands and older adults in the United States. Methods: We used data on 6107 respondents aged 65 and older in the baseline wave of the population‐based and harmonized 10/66 survey from Cuba, the Dominican Republic, and Puerto Rico, collected between 2003 and 2008, and 11, 032 respondents aged 65 and older from the U.S.‐based Health and Retirement Study data in 2014, a total of 17, 139 individuals. We estimated multivariable logistic regression models examining the association between education and dementia, adjusted for age, income, assets, and occupation. The models were estimated separately for the Caribbean population (pooled and by setting) and the U.S. population by race/ethnicity (Hispanic, Black, and White), followed by pooled models across all populations Results: In the Caribbean population, the relative risk of dementia among low versus high educated adults was 1.45 for women (95% confidence interval [CI] 1.17, 1.74) and 1.92 (95% CI 1.35, 2.49) for men, smaller compared to those in the United States, especially among non‐Hispanic Whites (women: 2.78, 95% CI 1.94, 3.61; men: 5.98, 95% CI 4.02, 7.95). Discussion: The differential associations between education and dementia across the Caribbean and US settings may be explained by greater disparities in social conditions in the United States compared to the Caribbean, such as access to health care, healthy behaviors, and social stressors, which serve as potentially important mediators.